2003
DOI: 10.1074/jbc.m304713200
|View full text |Cite
|
Sign up to set email alerts
|

Compact Globular Structure of Thermus thermophilus Ribosomal Protein S1 in Solution

Abstract: Ribosomal protein S1 of Thermus thermophilus overexpressed in Escherichia coli cells has been isolated and subjected to studies by analytical sedimentation and differential scanning microcalorimetry techniques. It has been demonstrated that the protein of 60 kDa sediments at s ؊7 cm 2 /s), indicating its compact globular conformation under these conditions. The microcalorimetry study has shown the presence of a cooperative tertiary structure melting at 90°C, but with several (probably three) independent cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
3
10
0
Order By: Relevance
“…Several E. coli and Thermus thermophilus ribosomal 30 S subunits structures are known, but they were solved in the absence of S1 (18 -21). S1 was studied with low resolution techniques, such as small angle x-ray scattering (14), electron microscopy (22), or analytical sedimentation (23). But these studies were performed on different systems (isolated E. coli and T. thermophilus S1 for the SAXS and sedimentation experiments respectively; bound to E. coli ribosome for electron microscopy) and lead to contradictory results: an extended structure according to SAXS, a compact structure according to sedimentation and electron microscopy.…”
mentioning
confidence: 99%
“…Several E. coli and Thermus thermophilus ribosomal 30 S subunits structures are known, but they were solved in the absence of S1 (18 -21). S1 was studied with low resolution techniques, such as small angle x-ray scattering (14), electron microscopy (22), or analytical sedimentation (23). But these studies were performed on different systems (isolated E. coli and T. thermophilus S1 for the SAXS and sedimentation experiments respectively; bound to E. coli ribosome for electron microscopy) and lead to contradictory results: an extended structure according to SAXS, a compact structure according to sedimentation and electron microscopy.…”
mentioning
confidence: 99%
“…The geometry was discretized using structured grids (approximately 150,000 cells ensured grid independence). The diffusivity of FBS considered in the model was derived from the Svedberg [64] equation and calculated to be 8.705×10 −11 m 2 /s. Virtual MV3 melanoma cells were modeled as spheres chemotacting at a speed of 8 µm/hr after sensing a critical FBS concentration (10% of the initial FBS concentration in the outer well).…”
Section: Methodsmentioning
confidence: 99%
“…As a source of protein S1 we used the extreme thermophilic bacterium Thermus thermophilus [8]. Earlier it was shown that protein S1 from this organism is more compact and stable in solution as compared with its homologue from E. coli and, therefore, more attractive for structural investigations [9].…”
Section: Introductionmentioning
confidence: 99%